(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The emerging contentions of Artificial Intelligence (AI) in the academic landscape necessitate understanding the factors influencing teachers’ decision to integrate this nascent technology. However, research on this phenomenon remains extant, particularly in the K-12 setting. As a result, this descriptive-correlational study aims to identify the determinants of teachers’ integration of AI educational technologies. This work is grounded on the tenets of the Unified Theory of Acceptance and Use of Technology (UTAUT). A validated questionnaire was administered to senior high school teachers selected through total enumeration. The data gathered were subjected to regression analysis to measure the influence of manifold factors on teachers’ integration of AI. Results of the study reveal that teachers’ decision to integrate AI educational technologies is significantly determined by performance expectancy, effort expectancy, social influence, and facilitating conditions. The study underscores the importance of principal and collegial support, AI investment, and involvement of AI developers in successfully integrating AI into educational environments.